2017
DOI: 10.1016/j.jcyt.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The exciting prospects of new therapies with mesenchymal stromal cells

Abstract: From the outset, it was apparent that developing new therapies with mesenchymal stem/stromal cells (MSCs) was not a simple or easy task. Among the earliest experiments was administration of MSCs from normal mice to transgenic mice that developed brittle bones because they expressed a mutated gene for type 1 collagen isolated from a patient with osteogenesis imperfecta. The results prompted a clinical trial of MSCs in patients with severe osteogenesis imperfecta. Subsequent work by large numbers of scientists a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
93
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(95 citation statements)
references
References 49 publications
1
93
0
1
Order By: Relevance
“…36,37 Nanosized EVs enable communication between MSCs and immune cells and disseminate their parental components throughout the body via biological fluids. 38 Similar to MSCs, hUCMSC-derived EVs can home to rat nerve injuries as revealed by fluorescent imaging ( Figure 8). Although the precise molecular mechanisms through which MSC-EVs migrate into sites of injury remain incompletely defined, their high expression of migration-associated cytokines and chemokines 27,39 may account for their homing function.…”
Section: Discussionmentioning
confidence: 95%
“…36,37 Nanosized EVs enable communication between MSCs and immune cells and disseminate their parental components throughout the body via biological fluids. 38 Similar to MSCs, hUCMSC-derived EVs can home to rat nerve injuries as revealed by fluorescent imaging ( Figure 8). Although the precise molecular mechanisms through which MSC-EVs migrate into sites of injury remain incompletely defined, their high expression of migration-associated cytokines and chemokines 27,39 may account for their homing function.…”
Section: Discussionmentioning
confidence: 95%
“…At the turn of this century, the observation that bone marrow-derived cells regenerate infarcted myocardium and that human MSCs differentiate to a cardiomyocyte phenotype in the adult murine heart, catapulted MSCs from niche cell to potent repair cell capable of regenerating damaged organs 2. Since, multiple laboratory studies have demonstrated the repair potential of MSCs in the heart, brain, lung, kidney, gut, skin, etc 3. In the neonatal lung, two proof of concept studies in mouse and rat pups exposed to high oxygen concentrations ignited excitement about the lung protective effect of MSCs and its clinical potential: a single intravenous or intratracheal administration of rodent bone marrow-derived MSCs improved survival and attenuated lung injury, inflammation and pulmonary hypertension spurring new hope in neonatology 4 5.…”
Section: Mesenchymal Stromal Cells For Bronchopulmonary Dysplasia—a Nmentioning
confidence: 99%
“…MSCs have been employed extensively in cell therapy, which includes a plethora of preclinical research investigations as well as a significant number of clinical trials [10][11][12][13]. Safety and efficacy have been shown in many clinical trials.…”
mentioning
confidence: 99%
“…The notable examples include the immune-mediated inflammatory diseases, such as graftversus-host disease and systemic lupus erythematosus [14][15]. Improved function after MSC infusions in multiple disease conditions has been mostly attributed to immunomodulatory effects, as these cells secrete a variety of paracrine factors, which interact with immune cells resulting eventually in immunomodulation [10][11][12][13]. The mechanisms underlying the improvements after MSC infusion in COVID-19 patients also appeared to be the robust antiinflammatory activity of MSCs.…”
mentioning
confidence: 99%